Ink, composite material, photoelectric device, Mini-LED backlight module and display device

By using composite ink of metal complexes and metal oxides in the electron transport layer, the problems of poor solution stability and agglomeration in the prior art are solved, better stability and film formation uniformity are achieved, and the performance and life of optoelectronic devices are improved.

CN119677387APending Publication Date: 2025-03-21TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311216409.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing metal oxide nanoparticle solution used to make electron transport layers has poor stability and is prone to agglomeration, which affects the stability of the ink and the uniformity of the film formation.

Method used

A composite ink including a metal complex and a metal oxide is provided to promote electron conduction and reduce charge accumulation through the tetragonal molecular structure of the metal complex and a highly delocalized electron structure.

Benefits of technology

It improves the stability and film formation uniformity of ink, enhances electron conduction capabilities, and extends the life and stability of optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677387A_ABST
    Figure CN119677387A_ABST
Patent Text Reader

Abstract

The invention discloses ink, a composite material, a photoelectric device, a Mini-LED backlight module and a display device. The ink provided by the invention comprises the metal complex, the metal oxide and the solvent, and has relatively good stability and film-forming uniformity; when the ink provided by the invention is used for manufacturing the electron transport layer, electron conduction in the electron transport layer can be promoted, charge accumulation and electron accumulation in the electron transport layer are reduced, and the material stability and the performance stability of the electron transport layer are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to an ink, a composite material, an optoelectronic device, a Mini-LED backlight module and a display device. Background Art

[0002] Various optoelectronic devices such as OPV, OFET, perovskite solar cells, organic electrophotonic devices (OLED), quantum dot electrophotonic devices (QLED), etc. contain an electron transport layer, which promotes the transmission and injection of electrons.

[0003] At present, most optoelectronic devices use wide-bandgap metal oxides such as zinc oxide (ZnO) as electron transport layer materials. They not only have excellent electron transport capabilities and high visible light transmittance, but also have abundant material sources and simple synthesis methods, and are widely used in the research of optoelectronic devices. However, when making electron transport layers, the stability of metal oxide nanoparticle solutions is poor and they are prone to agglomeration, which greatly affects the stability of the ink and the uniformity of film formation, thus affecting the performance of the film layer, and further affecting the life and stability of optoelectronic devices.

[0004] Therefore, the ink currently used to make the electron transport layer has the problems of poor solution stability and easy agglomeration. Summary of the invention

[0005] In view of this, the present application provides an ink, a composite material, an optoelectronic device, a Mini-LED backlight module and a display device, aiming to solve the technical problems of poor solution stability and easy agglomeration in the current ink for making electron transport layers.

[0006] The embodiment of the present application is implemented as follows: In a first aspect, an ink is provided, comprising a metal complex, a metal oxide and a solvent, wherein the structure of the metal complex is as shown in formula (I):

[0007] (I); wherein M is selected from transition metals; R1-R4 are each independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano; a combination of one or more of unsubstituted or substituted halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, -N(R5)2, C1-C30 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms; Each R5 is selected from a combination of one or more of hydrogen, deuterium, unsubstituted or substituted with halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms.

[0008] In a second aspect, an embodiment of the present application provides a composite material, comprising a metal complex and a metal oxide, wherein the structure of the metal complex is as shown in formula (I):

[0009] (I); wherein M is selected from transition metals; R1-R4 are each independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano; a combination of one or more of unsubstituted or substituted halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, -N(R5)2, C1-C30 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms; Each R5 is selected from a combination of one or more of hydrogen, deuterium, unsubstituted or substituted with halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms.

[0010] In a third aspect, an embodiment of the present application further provides a photoelectric device, comprising a first electrode and a second electrode arranged opposite to each other; and an electronic functional layer arranged between the first electrode and the second electrode; wherein the material of the electronic functional layer comprises the above-mentioned composite material.

[0011] In a fourth aspect, the present application further proposes a Mini-LED backlight module, the Mini-LED backlight module comprising a backplane and a plurality of optoelectronic devices arranged on one side of the backplane, the optoelectronic devices comprising the optoelectronic devices as described above, and the optoelectronic devices are Mini-LED chips. In a fifth aspect, an embodiment of the present application further provides a display device, comprising the above-mentioned optoelectronic device, or comprising the Mini-LED backlight module as described above.

[0012] The ink of the present application comprises a composite material and a solvent, wherein the composite material comprises a metal complex and a metal oxide, and the ink has good stability and film-forming uniformity. Moreover, after the ink is formed into a film, since the metal complex has a tetragonal molecular structure and a highly delocalized electronic structure, the spin density of its unpaired electrons is distributed on the entire anion skeleton, the π orbitals between adjacent coordinated anions overlap, and a composite material is formed with the metal oxide, which can promote electron conduction, and enhance the conduction and diffusion of electrons outside the composite material, reduce charge accumulation and electron accumulation in the composite material, and improve the material stability and performance stability of the film layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0014] Figure 1 A schematic structural diagram of an embodiment of a photoelectric device provided in the present application; Reference numerals: optoelectronic device 100 , first electrode 10 , second electrode 20 , electron functional layer 30 , electron transport layer 31 , electron injection layer 32 , light emitting layer 40 , hole functional layer 50 , hole transport layer 51 , hole injection layer 52 . DETAILED DESCRIPTION

[0015] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.

[0016] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0017] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0018] In the present application, "alkyl" may represent a straight chain, branched chain and / or cyclic alkyl. The carbon number of the alkyl group may be 1 to 10 or 1 to 6. A phrase containing the term, for example, "C1-10 alkyl" refers to an alkyl group containing 1 to 10 carbon atoms, each occurrence of which may be independently C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, C8 alkyl, C9 alkyl or C10 alkyl. Non-limiting examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, 2-ethylbutyl, 3,3-dimethylbutyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, cyclopentyl, 1-methylpentyl, 3-methylpentyl, 2-ethylpentyl, 4-methyl-2-pentyl, n-hexyl, 1-methylhexyl, 2-ethylhexyl, 2-butylhexyl, cyclohexyl, 4- One or more of methylcyclohexyl, 4-tert-butylcyclohexyl, n-heptyl, 1-methylheptyl, 2,2-dimethylheptyl, 2-ethylheptyl, 2-butylheptyl, n-octyl, tert-octyl, 2-ethyloctyl, 2-butyloctyl, 2-hexyloctyl, 3,7-dimethyloctyl, cyclooctyl, n-nonyl, n-decyl, adamantyl, 2-ethyldecyl, 2-butyldecyl, 2-hexyldecyl, and 2-octyldecyl.

[0019] In the present application, when the same substituent appears multiple times, it can be independently selected from different groups. For example, formula (I) may contain 4 R1s, and each R1 can be independently selected from different groups.

[0020] During the operation of optoelectronic devices, there may be charge accumulation in the electron transport layer. The accumulation of electrons in the electron transport layer will cause the electron transport layer to be charged, thus affecting the material stability of the electron transport layer. Therefore, how to improve the stability of the electron transport material is also a major problem. The present application provides an ink, comprising a composite material and a solvent, wherein the composite material comprises a metal complex and a metal oxide, and the structure of the metal complex is shown in formula (I):

[0021] (I); wherein M is selected from transition metals; R1-R4 are each independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano; a combination of one or more of unsubstituted or substituted halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, -N(R5)2, C1-C30 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms; Each R5 is selected from a combination of one or more of hydrogen, deuterium, unsubstituted or substituted with halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms.

[0022] In this embodiment, the composite material formed by the metal complex and the metal oxide in the ink can solve the problem that the metal oxide nanoparticle solution prepared with a pure solvent has poor stability and easy agglomeration, so that the ink has better stability and film-forming uniformity.

[0023] Furthermore, after the ink is formed into a film, since the metal complex has a tetragonal molecular structure and a highly delocalized electronic structure, the spin density of its unpaired electrons is distributed on the entire anion skeleton, and the π orbitals between adjacent coordinated anions overlap, forming a composite material with the metal oxide, which can promote electron conduction, and enhance the conduction and diffusion of electrons outside the composite material, reduce charge accumulation and electron accumulation in the composite material, and improve the material stability and performance stability of the film layer.

[0024] The solvent may be one or more of alcohol solvents such as ethanol, isopropanol, and n-butanol. That is, the solvent may be a single solvent or a mixed solvent formed by multiple solvents. It is understandable that the above alcohol solvents are only an enumeration of solvent types, and the solvent is not limited to the above solvent types.

[0025] In one embodiment, the sum of the concentrations of the metal complex and the metal oxide is 20-50 mg / mL, that is, the concentration of the composite material is 20-50 mg / mL, specifically 20-40 mg / mL, 30-40 mg / mL, 30-33 mg / mL, 33-35 mg / mL, 35-40 mg / mL, etc. The ink in the concentration range can have good dispersibility and film-forming uniformity, and can also avoid excessive use of solvents to cause solvent waste.

[0026] The composite material in the ink may refer to the related description of the composite material below, which will not be described in detail here.

[0027] The present application provides a composite material, comprising a metal complex and a metal oxide, wherein the structure of the metal complex is as shown in formula (I):

[0028] (I); wherein M is selected from transition metals; R1-R4 are each independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano; a combination of one or more of unsubstituted or substituted halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, -N(R5)2, C1-C30 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms; Each R5 is selected from a combination of one or more of hydrogen, deuterium, unsubstituted or substituted with halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms.

[0029] In this embodiment, the metal complex has a planar tetragonal molecular structure and a highly delocalized electronic structure, the spin density of its unpaired electrons is distributed on the entire anion skeleton, and the π orbitals between adjacent coordinated anions overlap, which can promote electron conduction, thereby enhancing the conduction and diffusion of electrons outside the composite material, significantly reducing the charge accumulation and electron accumulation in the composite material, offsetting the effects of excessive electron injection, and improving the stability of the composite material during application.

[0030] Furthermore, in one embodiment, R1-R4 are each independently selected from a combination of one or more of an aryl group having 5 to 18 ring atoms and a heteroaryl group having 5 to 18 ring atoms, which are unsubstituted or substituted with one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, thiol, cyano, C1-C10 alkyl, C1-C10 alkoxy, and -N(R5)2.

[0031] Wherein, the C1-10 alkyl group includes one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, isobutyl, 2-ethylbutyl, 3,3-dimethylbutyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, cyclopentyl, n-nonyl and n-decyl.

[0032] Further, each R5 can be selected from a combination of one or more of hydrogen, deuterium, unsubstituted or substituted with halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1~C10 alkyl, C3~C10 cycloalkyl, C1~C10 alkoxy, aryl having 5 to 18 ring atoms, heteroaryl having 5 to 18 ring atoms, aryloxy having 5 to 18 ring atoms, and heteroaryloxy having 5 to 18 ring atoms.

[0033] In one embodiment, the structure of the metal complex is shown in formula (II):

[0034] (II); Wherein, R6-R9 are each independently selected from one or more combinations of hydrogen, deuterium, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, -N(R5)2; Each R5 is selected from hydrogen, deuterium, C1-C10 alkyl which is unsubstituted or substituted by one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano.

[0035] In one embodiment, the transition metal M includes one or more of Ni, Zr, Ti, Cr, Pd, Pt, Co, and Mo, that is, one or more of nickel, zirconium, titanium, chromium, palladium, platinum, cobalt, and molybdenum.

[0036] In a specific embodiment, the transition metal M is selected from Ni, and the structure of the metal complex is one or more of the following:

[0037]

[0038] .

[0039] In one embodiment, the direct band gap of the metal oxide is 2.0-6.0 eV, specifically 2.0-5.0 eV, 3.0-5.0 eV, 3.0-4.0 eV, 2.0-3.0 eV, 5.0-6.0 eV, etc. Further, the metal oxide includes one or more of zinc oxide, zirconium oxide, titanium oxide, zirconium oxide, etc. The above metal oxides have electron migration ability and can be used as carrier transport materials in the optoelectronic device 100.

[0040] Furthermore, the metal oxide may also include doping elements, and the doping elements include one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y.

[0041] In one embodiment, the average particle size of the metal oxide can be 2~15nm, specifically 2~3nm, 2~5nm, 2~6nm, 2~8nm, 2~10nm, 2~12nm, 2~15nm, 3~5nm, 3~6nm, 3~8nm, 3~10nm, 3~12nm, 3~15nm, 5~6nm, 5~8nm, 5~10nm, 5~12nm, 5~15nm, 6~8nm, 6~10nm, 6~12nm, 6~15nm, 8~10nm, 8~12nm, 8~15nm, 10~12nm, 10~15nm, 12~15nm, etc.

[0042] In a specific embodiment, the average particle size of the metal oxide is preferably 2 to 8 nm. The metal oxide with a smaller particle size or smaller particles can be better mixed with the metal complex, thereby increasing the effective contact area between the two, promoting electron conduction, and improving the material stability of the composite material.

[0043] It can be understood that the metal oxide is a nanoparticle, and its specific shape can be nanospheres, nanosheets, nanorods, etc.

[0044] In this embodiment, the metal complex includes a benzene ring group with high electron cloud density, which can be adsorbed onto the metal oxide. The metal complex has a planar tetragonal molecular structure and a highly delocalized electronic structure, and the spin density of its unpaired electrons is distributed on the entire anion skeleton. The π orbitals between adjacent coordinated anions overlap, which can promote electron conduction, thereby enhancing the conduction and diffusion of electrons outside the composite material, significantly reducing the charge accumulation and electron accumulation in the composite material, offsetting the effects of excessive electron injection, and improving the stability of the composite material during application.

[0045] In one embodiment, the mass ratio of the metal complex to the metal oxide is (1-3):20, that is, based on the weight of the metal oxide, the metal complex accounts for 5-15% of the mass of the metal oxide, specifically 5-6%, 5-8%, 5-9%, 5-10%, 5-12%, 5-15%, 6-8%, 6-9%, 6-10%, 6-12%, 6-15%, 8-9%, 8-10%, 8-12%, 8-15%, 9-10%, 9-12%, 9-15%, 10-12%, 10-15%, 12-15%, etc. The mass ratio of the metal complex to the metal oxide can make the composite material have better electron mobility, and also reduce the charge accumulation and electron accumulation of the composite material when it is used in a device.

[0046] In a specific embodiment, the mass ratio of the metal complex to the metal oxide is (1~2):20, i.e., 5~10%. The composite material can better promote electron conduction, reduce charge accumulation and electron accumulation in the composite material, and offset the effects of excessive electron injection, so that the composite material can maintain its original high electron transport performance, thereby improving the working life and stability of the light-emitting device. In addition, the mass proportion of the metal oxide is relatively high, so that the composite material has better electron mobility, thereby having better luminous efficiency and other luminous properties.

[0047] In one embodiment, the composite material is a mixed material formed by the metal complex and the metal oxide. In this embodiment, the mixing of the metal complex and the metal oxide can improve the contact and adsorption connection between the two. Specifically, the S atoms in the metal complex can connect to the metal atoms in the metal oxide. When the metal oxide is charged, the electrons can be quickly transferred to the transition metal M atoms therein, and through other metal oxides connected to other S atoms in the metal complex, the charges can be quickly diffused to reduce charge accumulation.

[0048] In one embodiment, the composite material can be prepared by the following steps: mixing the metal complex and the metal oxide in a solvent according to a certain proportion, and drying to remove the solvent to obtain the composite material.

[0049] Wherein, the solvent may be an alcohol solvent such as ethanol, isopropanol, n-butanol, etc. The drying may be vacuum drying or heating drying to remove the solvent as much as possible. Wherein, the pressure of the vacuum drying may be 0.01~10Pa, and the time may be 5~30 min. The temperature of the heating drying may be 40~150°C, and the time may be 5~60 min. Specifically, the pressure of the vacuum drying may be 0.01~0.1Pa, 0.1~1Pa, 1~5Pa, 5~10Pa, etc., and the time may be 5~10min, 10~20min, 20~30min, etc. Specifically, the temperature of the heating drying may be 40~12°C, 60~120°C, 60~100°C, 80~100°C, 100~150°C, etc., and the time may be 5~10min, 10~20 min, 20~30 min, 30~40min, 40~50min, 50~60 min, etc.

[0050] See also Figure 1 , Figure 1 The schematic diagram of the structure of an embodiment of the optoelectronic device provided in the present application. The optoelectronic device 100 includes a first electrode 10, a second electrode 20 and an electronic functional layer 30, wherein the first electrode 10 and the second electrode 20 are arranged opposite to each other, and the electronic functional layer 30 is arranged between the first electrode 10 and the second electrode 20. The electronic functional layer 30 is prepared by the ink provided in the present application, or the material of the electronic functional layer 30 includes the composite material provided in the present application.

[0051] In this embodiment, the electronic functional layer 30 is prepared by the ink provided by the present application, or the composite material is used in the electronic functional layer 30, which can promote electron conduction, thereby enhancing the conduction and diffusion of electrons outside the electronic functional layer 30, significantly reducing the charge accumulation and electron accumulation in the electronic functional layer 30, offsetting the impact of excessive electron injection, so that the composite material can maintain its original high electron transmission performance, thereby improving the working life and stability of the optoelectronic device 100.

[0052] When the optoelectronic device 100 is a light-emitting device, the efficiency of electron transfer to the light-emitting layer can be improved, so that the exciton recombination centers are gathered in the light-emitting layer, thereby improving the recombination efficiency and the light-emitting efficiency.

[0053] In a specific embodiment, the electronic functional layer 30 is made of the composite material.

[0054] In one embodiment, the optoelectronic device 100 includes a light-emitting layer 40 , and the light-emitting layer 40 is disposed between the electronic functional layer 30 and the first electrode 10 , or between the electronic functional layer 30 and the second electrode 20 .

[0055] The first electrode 10 and the second electrode 20 are a pair of electrodes, one of which is an anode and the other is a cathode. It can be understood that the electronic functional layer 30 is disposed between the light emitting layer 40 and the cathode.

[0056] In one embodiment, the electronic functional layer 30 includes one or more layers of an electron transport layer 31 and an electron injection layer 32, and the electron injection layer 32 is disposed close to the cathode. The material of the electron transport layer 31 and / or the electron injection layer 32 includes the composite material.

[0057] In one embodiment, the electron transport layer 31 is composed of the composite material. The thickness of the electron transport layer 31 may be 20-80 nm, specifically 30-80 nm, 30-60 nm, 50-60 nm, etc.

[0058] In one embodiment, the electronic functional layer 30 includes only one electron transport layer 31 .

[0059] In a specific embodiment, the material of the electron transport layer 31 includes the composite material.

[0060] In a specific embodiment, the preparation method of the electron transport layer includes: providing ink, the ink is the ink provided in this application or the ink formed by the composite material and solvent provided in this application, setting the ink on a prefabricated device or substrate, and drying to obtain the electron transport layer 31. Among them, the ink can be set by a solution method known in the art, such as spin coating, coating, inkjet printing, scraping, dip pulling, soaking, spraying, rolling or casting. Specifically, the drying process can refer to the conventional drying process steps in the following text, which will not be repeated here.

[0061] Furthermore, the material of the electron injection layer 32 is a material known in the art for electron injection layer, for example, it can be selected from but not limited to at least one of LiF, LiF / Yb, MgP, MgF2, Al2O3, Ga2O3, ZnO, Cs2CO3, Rb2CO3, and RbBr.

[0062] In one embodiment, the optoelectronic device 100 further includes a hole functional layer 50, which is disposed between the light emitting layer 40 and the anode. The hole functional layer 50 includes one or more layers of a hole transport layer 51 and a hole injection layer 52.

[0063] The material of the hole transport layer 51 may include poly(9,9-dioctylfluorene-co-N-(4-butylphenyl) diphenylamine) (TFB), polyvinylcarbazole (PVK), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl) benzidine) (poly-TPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4',4''-tri(carbazole-9-yl) triphenylamine (TCATA), 4,4'-bis(9-carbazole) biphenyl (CBP), N,N'-diphenyl-N,N'- One or more of di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) (PEDOT:PSS), Spiro-NPB, Spiro-TPD, doped or undoped NiO, MoO3, WO3, V2O5, P-type gallium nitride, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN.

[0064] The material of the hole injection layer 52 is a material with hole injection capability, and may include one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN), copper phthalocyanine (CuPc), transition metal oxide particles, and transition metal sulfur compounds; wherein the transition metal oxide particles include one or more of NiO, MoO2, WO3, and CuO; and the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, and CuS.

[0065] In one embodiment, the material of the light-emitting layer 40 may be selected from one or more of organic light-emitting materials or quantum dot materials; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light; The quantum dot material is selected from at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, Cd At least one of HgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe; the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe; the I Group II-V compounds are selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, I nNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, In At least one of AlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dot with core-shell structure is selected from any one of the above-mentioned single structure quantum dots, and the shell material of the quantum dot with core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductor, or organic-inorganic hybrid perovskite semiconductor; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs +ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2 + Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .

[0066] When n=2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.

[0067] In a specific embodiment, the material of the light-emitting layer 40 is selected from the core-shell structured quantum dots.

[0068] In one embodiment, the quantum dot material is an oil-soluble quantum dot, specifically including binary phase, ternary phase, and quaternary phase quantum dots; wherein the binary phase quantum dots include CdS, CdSe, CdTe, InP, AgS, PbS, PbSe, HgS, etc., but are not limited thereto; the ternary phase quantum dots include Zn X Cd 1-X S, Cu X In 1-X S, Zn X Cd 1-X Se, Zn X Se 1-X S, Zn X Cd 1-X Te、PbSe X S 1-X The quaternary phase quantum dots include, but are not limited to, Zn X Cd 1-X S / ZnSe、Cu X In 1-X S / ZnS, Zn X Cd 1-X Se / ZnS, CuInSeS, Zn X Cd 1- X Te / ZnS、PbSe X S 1-X / ZnS etc. are not limited thereto.

[0069] In one embodiment, the quantum dot material is an oily quantum dot, and the oily quantum dot is coordinated and connected with a ligand, so as to increase the solubility of the quantum dot material in an organic solvent, such as making the quantum dot material soluble in a solvent with lower polarity. Wherein, the ligand includes at least one of an acid ligand, a thiol ligand, an amine ligand, a (oxygen) phosphine ligand, a phospholipid, a soft phosphine, and polyvinyl pyridine. As a specific embodiment, the acid ligand is at least one of deca-acid, undecylenic acid, tetradecanoic acid, oleic acid, and stearic acid; the thiol ligand is at least one of octadecyl mercaptan, dodecyl mercaptan, and octadecyl mercaptan; the amine ligand includes at least one of oleylamine, octadecylamine, and octadecylamine; the (oxygen) phosphine ligand is at least one of trioctylphosphine and trioctylphosphine oxide. Specifically, the quantum dot material can be configured into quantum dot ink for use. In the quantum dot ink, the concentration of quantum dots is 10~100 mg / mL, for example, 10~20 mg / mL, 20~50 mg / mL, 50~100 mg / mL, etc. Within this concentration range, the solution processing performance of quantum dots is better and the dispersibility is better.

[0070] It can be understood that when the material of the light-emitting layer 40 is an organic light-emitting material, the optoelectronic device 100 is an organic electrophotoelectric device. When the material of the light-emitting layer 40 is a quantum dot light-emitting material, the optoelectronic device 100 is a quantum dot electrophotoelectric device.

[0071] In one embodiment, the first electrode 10 and the second electrode 20 are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide particle electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide particle electrode is selected from at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS and ZnS / Al / ZnS. Here, “ / ” represents a stacked structure. For example, the composite electrode AZO / Ag / AZO represents an electrode with a composite structure of three stacked layers consisting of an AZO layer, an Ag layer and an AZO layer.

[0072] Specifically, the thickness of the first electrode 10 may be 10-1000 nm, specifically 30-100 nm, 10-800 nm, 100-800 nm, 100-600 nm, 200-600 nm, 200-400 nm, etc. The thickness of the second electrode 20 may be 10-1000 nm, specifically 30-100 nm, 10-800 nm, 100-800 nm, 100-600 nm, 200-600 nm, 200-400 nm, etc.

[0073] It is understood that, in addition to the above-mentioned functional layers, the optoelectronic device 100 may also be provided with some functional layers conventionally used in optoelectronic devices that help improve the performance of the optoelectronic device, such as an electron blocking layer, a hole blocking layer, an interface modification layer, etc. It is understood that the material and thickness of each layer of the optoelectronic device 100 may be adjusted according to the light emission requirements of the optoelectronic device 100.

[0074] It can be understood that the material and thickness of each layer of the optoelectronic device 100 can be set and adjusted accordingly according to the performance requirements of the optoelectronic device 100, such as light emission requirements.

[0075] The optoelectronic device 100 further includes a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.

[0076] It can be understood that the photoelectric device 100 can be an upright photoelectric device or an inverted photoelectric device. When the photoelectric device 100 is an upright photoelectric device, the substrate is combined with the side of the anode away from the light-emitting layer 40. When the photoelectric device 100 is an inverted photoelectric device, the substrate is combined with the side of the cathode away from the light-emitting layer 40.

[0077] It should be noted that the first electrode 10, the second electrode 20, the light-emitting layer 40 and other functional layers in the present application can be prepared by conventional techniques in the art, including but not limited to solution method and deposition method, wherein the solution method includes but is not limited to spin coating, coating, inkjet printing, scraping, dip pulling, immersion, spraying, rolling or casting; the deposition method includes chemical method and physical method, the chemical method includes but is not limited to chemical vapor deposition, continuous ion layer adsorption and reaction method, anodization method, electrolytic deposition method or coprecipitation method, and the physical method includes but is not limited to thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method or pulsed laser deposition method. When the first electrode 10, the second electrode 20, the electronic functional layer 30, the light-emitting layer 40 and other functional layers are prepared by the solution method, a drying process needs to be added.

[0078] Specifically, the drying process can be vacuum drying or heating drying to remove the solvent as much as possible. Among them, the pressure of the vacuum drying can be 0.01~10Pa, and the time is 5~30 min. The temperature of the heating drying can be 40~150℃, and the time is 5~60 min. Specifically, the pressure of the vacuum drying can be 0.01~0.1Pa, 0.1~1Pa, 1~5Pa, 5~10Pa, etc., and the time can be 5~10min, 10~20 min, 20~30 min, etc. Specifically, the temperature of the heating drying can be 40~12℃, 60~120℃, 60~100℃, 80~100℃, 100~150℃, etc., and the time can be 5~10min, 10~20 min, 20~30 min, 30~40min, 40~50 min, 50~60 min, etc.

[0079] The drying process in the present application may be an annealing process. "Annealing process" includes all treatment processes that can make the wet film obtain higher energy, thereby changing from a wet film state to a dry state. For example, "annealing process" may only refer to a heat treatment process, that is, heating the wet film to a specific temperature, and then maintaining it for a specific time to allow the solvent in the wet film to fully evaporate; for example, "annealing process" may also include a heat treatment process and a cooling process performed in sequence, that is, heating the wet film to a specific temperature, and then maintaining it for a specific time to allow the solvent in the first wet film to fully evaporate, and then cooling it at an appropriate speed to eliminate residual stress and reduce the risk of layer deformation and cracks in the dried film.

[0080] It is understood that the method for preparing the optoelectronic device may further include a packaging step, and the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with UV curing glue. The concentrations of oxygen and water in the environment of the packaging step are both lower than 0.1ppm to ensure the stability of the optoelectronic device.

[0081] In some other embodiments, the optoelectronic device 100 is a Mini-LED chip. The Mini-LED chip includes a sapphire substrate, a hole transport layer 51, a light-emitting layer 40, an electronic functional layer 30, a first electrode 10 and a second electrode 20, wherein the first electrode 10 and the second electrode 20 are both arranged on a side of the electronic functional layer 30 away from the light-emitting layer 40 and are spaced apart from each other.

[0082] It can be understood that the electronic functional layer 30 can be a single-layer structure formed of a composite material, or a stacked structure of two or more layers, such as a film layer formed of a composite material, a film layer formed of other electronic functional materials, etc.

[0083] When the optoelectronic device 100 is a Mini-LED chip, since it has a relatively high service life and stability, the service life and stability of the Mini-LED chip can also be improved when preparing a Mini-LED backlight module.

[0084] In some embodiments, the method for preparing the Mini-LED chip may include the following steps: providing a sapphire substrate; using the MOCVD method to sequentially grow a hole transport layer 51 on the sapphire substrate, and then sequentially preparing a light-emitting layer 40 and an electronic functional layer 30; evaporating a first electrode 10 and a second electrode 20 on the electronic functional layer 30 to obtain a Mini-LED chip.

[0085] In a specific embodiment, the preparation method of the Mini-LED chip is: Providing a sapphire substrate; Using the MOCVD method, p-GaN (P-type gallium nitride) is grown on a sapphire substrate to obtain a hole transport layer 51; Spin-coat the blue quantum dot material CdSe on the hole transport layer 51 to form the light-emitting layer 40; Spin coating n-GaN on the light emitting layer 40 to form a first layer, and then spin coating the composite material on the first layer to form an electronic functional layer 30 having a two-layer stacked structure; or, spin coating the composite material on the light emitting layer 40 to form a first layer, and then spin coating n-GaN on the first layer to form an electronic functional layer 30 having a two-layer stacked structure; Al is evaporated on the electronic functional layer 30 to form a first electrode, and Au is evaporated on the interface modification layer 30 to form a second electrode. The first electrode and the second electrode are spaced apart from each other to obtain a Mini-LED chip.

[0086] In a fourth aspect, the present application also proposes a Mini-LED backlight module, which includes a backplane and a plurality of optoelectronic devices 100 arranged on one side of the backplane, wherein the optoelectronic devices 100 include the optoelectronic devices described above, and the optoelectronic devices 100 are Mini-LED chips.

[0087] In some embodiments, multiple Mini-LED chips are distributed in an array.

[0088] The present application also relates to a display device, which includes the composite material provided by the present application, or the optoelectronic device 100 provided by the present application, or includes the Mini-LED backlight module provided by the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0089] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0090] Example 1 This embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.

[0091] Step 1: Pretreatment of ITO glass substrate (the thickness of the ITO layer is 120 nm): Clean the ITO glass substrate with a detergent to preliminarily remove stains on the surface, then ultrasonically clean it in deionized water, acetone, anhydrous ethanol, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally blow dry it with high-purity nitrogen.

[0092] Step 2: Spin-coat PEDOT:PSS (mass fraction of 2.8%, molar ratio of PEDOT to PSS of 1:1) on the ITO substrate at a speed of 4000 rpm for 30 seconds, and then heat on a heating plate at 150°C for 20 minutes to obtain a hole injection layer with a thickness of 80 nm.

[0093] Step 3: In an inert atmosphere, spin-coat TFB (concentration of 8 mg / mL) on the hole injection layer at a speed of 3000 rpm for 30 s, and then heat on a hot plate at 120°C for 20 min to obtain a hole transport layer with a thickness of 70 nm.

[0094] Step 4: Spin-coat CdSeS / ZnS green quantum dot solution (concentration of 30 mg / mL, with octanethiol ligands attached to the surface, and 0.2 mmol of ligands for every 1 mg of quantum dots) on the hole transport layer at a speed of 3000 rpm for 30 s, and then heat on a heating plate at 80°C for 5 min to obtain a light-emitting layer with a thickness of 70 nm.

[0095] Step 5: Provide ink for an electron transport layer, the ink consisting of a composite material and ethanol, wherein the composite material includes zinc oxide ZnO with a particle size of 2 to 5 nm and a metal complex 1, the mass ratio of the two is 10:1, the total concentration of the composite material is 33 mg / mL, and the structure of the metal complex 1 is as follows; set the composite material ethanol solution on the light-emitting layer, and then heat it at 80°C for 10 minutes to obtain an electron transport layer with a thickness of 50 nm.

[0096] Step 6: By thermal evaporation, the vacuum degree is not higher than 3×10 -4 Pa, Al was evaporated on the electron transport layer at a rate of 1 angstrom / second for 200 seconds to obtain a second electrode with a thickness of 60 nm, and then packaged to obtain a quantum dot light-emitting diode.

[0097] Among them, the structure of metal complex 1 is as follows, and its preparation process refers to the preparation process in "J. Am. Chem. Soc. 2020,142, 48, 20313-20317", DOI: 10.1021 / jacs.0c09009.

[0098]

[0099] Metal complex 1.

[0100] Example 2 This embodiment is basically the same as the embodiment 1, and the only difference is that in step 5, the metal complex 2 used on the light-emitting layer replaces the metal complex 1.

[0101] Among them, the structure of metal complex 2 is as follows, and its preparation process refers to the preparation process in the reference "Theranostics 2020; 10(6):2509-2521. doi: 10.7150 / thno.39403".

[0102]

[0103] Metal complex 2.

[0104] Example 3 This embodiment is basically the same as the embodiment 1, and the only difference is that in step 5, the metal complex 3 used on the light-emitting layer replaces the metal complex 1.

[0105]

[0106] Metal complex 3 Example 4 This embodiment is basically the same as the embodiment 1, and the only difference is that in step 5, the metal complex 4 used on the light-emitting layer replaces the metal complex 1.

[0107]

[0108] Metal complex 4 Example 5 This embodiment is basically the same as the embodiment 1, and the only difference is that in step 5, the metal complex 5 used on the light-emitting layer replaces the metal complex 1.

[0109]

[0110] Metal complex 5 Among them, the preparation process of metal complexes 3-5 refers to the preparation process in the reference “Eur. J. Inorg. Chem. 10.1002 / ejic.201900886”.

[0111] Example 6 This embodiment is substantially the same as embodiment 1, except that in step 5, the mass ratio of zinc oxide to metal complex 1 is 20:1.

[0112] Example 7 This embodiment is substantially the same as embodiment 1, except that in step 5, the mass ratio of zinc oxide to metal complex 1 is 20:3.

[0113] Example 8 This embodiment is basically the same as Embodiment 1, except that the average particle size of zinc oxide is 5-8 nm.

[0114] Example 9 This embodiment is basically the same as Embodiment 1, except that the average particle size of zinc oxide is 12-15 nm.

[0115] Device Comparative Example 1 This device embodiment is substantially the same as device embodiment 1, with the only difference being that in step 5, zinc oxide is disposed on the light-emitting layer to prepare an electron transport layer.

[0116] Test: The quantum dot light-emitting diodes of device embodiments 1-9 and device comparative example 1 were subjected to performance tests, and the test indicators and test methods were as follows: Luminous efficiency CE-1knit (cd / A): measured using optical testing instruments; Device lifespan T95-1knit (h): refers to the lifespan of the device when the brightness decays to 95% at a starting brightness of 1000 nits; Device on / off efficiency fluctuation: The efficiency change of the device when it is turned off for 1 minute and then restarted when it is operated at 1000 nits; The initial voltage and T95 voltage are the voltage when the device starts operating at 1000 nits and the voltage when the brightness of the device decays to 95%, respectively.

[0117] Table 1

[0118] It can be seen from Table 1 that compared with Comparative Example 1, the light-emitting devices of Examples 1-9 have better lifespan and device efficiency, and the voltage basically does not change before the device life reaches T95, indicating that the light-emitting device has good working stability. This may be because the electron transport layer is formed by the ink provided in the present application and has good film uniformity. The material in the electron transport layer includes the composite material provided in the present application, which can promote the conduction and diffusion of electrons outside the electron transport layer, reduce the charge accumulation and electron accumulation in the electron transport layer, and offset the impact of excessive electron injection, so that the composite material can maintain the original high electron transport performance, thereby improving the working life and stability of the light-emitting device.

[0119] The light-emitting devices of Examples 1 and 6-7 all have better lifespan and stability. Compared with Example 7, the light-emitting devices of Examples 1 and 6 have better luminous efficiency CE-1knit while having a better lifespan. This may be because the mass proportion of metal oxide in the electron transport layer is relatively high, thereby improving the electron mobility of the electron transport layer, thereby improving the luminous efficiency of the light-emitting device.

[0120] Compared with Example 9, the light-emitting devices of Example 1 and Example 8 have a better lifespan, which may be due to the fact that the metal oxide particles are smaller (particle size ranges from 2 to 8 nm), and can be better mixed with the metal complex, thereby increasing the effective contact area between the two, and can further promote electron conduction, thereby improving the material stability of the composite material, enhancing the conduction and diffusion of electrons outside the composite material, reducing charge accumulation and electron accumulation in the composite material, and being able to offset the effects of excessive electron injection, so that the composite material can maintain its original high electron transmission performance, thereby improving the working life and stability of the light-emitting device.

[0121] The ink, composite material, optoelectronic device, Mini-LED backlight module and display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. An ink, characterized in that: It includes a metal complex, a metal oxide and a solvent, wherein the structure of the metal complex is as shown in formula (I): (I); wherein M is selected from transition metals; R1-R4 are each independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano; a combination of one or more of unsubstituted or substituted halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, -N(R5)2, C1-C30 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms; Each R5 is selected from a combination of one or more of hydrogen, deuterium, unsubstituted or substituted with halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms.

2. The ink according to claim 1, characterized in that R1-R4 are each independently selected from a combination of one or more of an aryl group having 5 to 18 ring atoms and a heteroaryl group having 5 to 18 ring atoms, which are unsubstituted or substituted with one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, and -N(R5)2; and / or, Each R5 is selected from a combination of one or more of hydrogen, deuterium, unsubstituted or substituted with halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C3-C10 cycloalkyl, C1-C10 alkoxy, aryl having 5 to 18 ring atoms, heteroaryl having 5 to 18 ring atoms, aryloxy having 5 to 18 ring atoms, and heteroaryloxy having 5 to 18 ring atoms; and / or, The transition metal includes one or more of Ni, Zr, Ti, Cr, Pd, Pt, Co, and Mo.

3. The ink according to claim 1, characterized in that The structure of the metal complex is shown in formula (II): (I); Wherein, R6-R9 are each independently selected from one or more combinations of hydrogen, deuterium, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, -N(R5)2; Each R5 is selected from hydrogen, deuterium, C1-C10 alkyl which is unsubstituted or substituted by one or more of halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano.

4. The ink according to claim 3, characterized in that The structure of the metal complex is one or more of the following: 。 5. The ink according to any one of claims 1 to 4, characterized in that The direct band gap of the metal oxide is 2.0 to 6.0 eV; and / or The metal oxide comprises one or more of zinc oxide, zirconium oxide, titanium oxide and zirconium oxide; and / or The metal oxide includes a doping element, and the doping element includes one or more of Mg, Ca, Li, Ga, Al, Co, Mn, Zr, W, Ti, and Y; and / or The average particle size of the metal oxide is 2 to 15 nm; and / or The mass ratio of the metal complex to the metal oxide is (1-3):20; and / or The solvent is selected from alcohol solvents; and / or In the ink, the sum of the concentrations of the metal complex and the metal oxide is 20-50 mg / mL.

6. The ink according to claim 5, characterized in that The average particle size of the metal oxide is 2 to 8 nm; and / or The mass ratio of the metal complex to the metal oxide is (1-2):20; and / or The alcohol solvent includes one or more of ethanol, isopropanol, and n-butanol.

7. A composite material, characterized in that It includes a metal complex and a metal oxide, wherein the structure of the metal complex is as shown in formula (I): (I); wherein M is selected from transition metals; R1-R4 are each independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, and cyano; a combination of one or more of unsubstituted or substituted halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C10 alkyl, C1-C10 alkoxy, -N(R5)2, C1-C30 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms; Each R5 is selected from a combination of one or more of hydrogen, deuterium, unsubstituted or substituted with halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, C3-C30 cycloalkyl, C1-C20 alkoxy, aryl having 5 to 60 ring atoms, heteroaryl having 5 to 60 ring atoms, aryloxy having 5 to 60 ring atoms, and heteroaryloxy having 5 to 60 ring atoms.

8. The composite material according to claim 7, characterized in that The composite material consists of the metal complex and the metal oxide; and / or The metal oxide comprises one or more of zinc oxide, zirconium oxide, titanium oxide and zirconium oxide; and / or The average particle size of the metal oxide is 2 to 8 nm; and / or The mass ratio of the metal complex to the metal oxide is (1-2):20; and / or The structure of the metal complex is one or more of the following: 。 9. A photoelectric device, characterized in that: include: A first electrode and a second electrode arranged opposite to each other; An electronic functional layer is arranged between the first electrode and the second electrode; wherein the electronic functional layer is prepared by the ink described in any one of claims 1-6, or the material of the electronic functional layer includes the composite material described in any one of claims 7-8.

10. The optoelectronic device according to claim 9, characterized in that: The optoelectronic device includes any one of OLED, QLED, Mini-LED chip and Micro-LED chip.

11. The optoelectronic device according to claim 10, characterized in that The electronic functional layer is composed of the composite material; and / or The thickness of the electronic functional layer is 20-80 nm; and / or The optoelectronic device comprises a light-emitting layer, which is arranged between the electronic functional layer and the first electrode, or between the electronic functional layer and the second electrode; wherein the material of the light-emitting layer is an organic light-emitting material or a quantum dot light-emitting material; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dots are selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, and the single-structure quantum dots are selected from II-VI compounds, IV- At least one of a Group VI compound, a Group III-V compound, and a Group I-III-VI compound, wherein the Group II-VI compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, Cd At least one of HgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP , at least one of GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is at least one selected from CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or The photoelectric device comprises a hole functional layer, wherein the hole functional layer comprises one or more layers of a hole transport layer and a hole injection layer, wherein the material of the hole transport layer comprises poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylene)diphenylamine, diamine), 4,4',4''-tri(carbazole-9-yl)triphenylamine, 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), Spiro-NPB, Spiro-TPD, doped or undoped NiO, MoO3, WO3, V2O5, P-type gallium nitride, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN, one or more of the hole injection layer comprising poly (3,4-ethylenedioxythiophene) -polystyrene sulfonic acid, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, transition metal oxide particles, transition metal sulfur compounds one or more, wherein the transition metal oxide particles include one or more of NiO, MoO2, WO3, CuO, the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, CuS; and / or The first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide particle electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide particle electrode is selected from at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS and ZnS / Al / ZnS.

12. A Mini-LED backlight module, characterized in that: The Mini-LED backlight module includes a backplane and a plurality of optoelectronic devices arranged on one side of the backplane, the optoelectronic devices include the optoelectronic devices as described in any one of claims 9 to 11, and the optoelectronic devices are Mini-LED chips.

13. A display device, characterized in that: The display device includes the optoelectronic device as described in any one of claims 9 to 11, or includes the Mini-LED backlight module as described in claim 12.